Pediatric Autoimmune Neuropsychiatric Disorder Associated with Streptococcus Immunology: A Pilot Study. (1st April 2015) - Walls, Andrew; Cubangbang, Maricel; Wang, Hongkun; Raiji, Manish; Knight, Josh; Steehler, Matthew; Latimer, Elizabeth; Harley, Earl H.
Abstract : Objective: To elucidate specific cytokine and chemokine markers in patients diagnosed with pediatric autoimmune neuropsychiatric disorder associated with streptococcus (PANDAS). Study Design: Prospective cohort study. Study setting: Academic university hospital. Methods: Tonsil tissue was collected from 24 patients and organized into 3 groups: experimental PANDAS cohort (12 patients), group A beta hemolytic streptococcus control cohort (6 patients), and obstructive sleep apnea control cohort (6 patients). Each tissue sample was extracted with MSD Tris lysis buffer, and protein lysates were analyzed for human chemokines and cytokines by the Human Cytokine 30‐Plex Assay on the Mesoscale System. Results: We identified a significant difference in expression regarding the 8 following cytokines when comparing the experimental PANDAS, group A beta hemolytic streptococcus, and obstructive sleep apnea control cohorts: tumor necrosis factor–α and eotaxin‐3. In addition, our group also identified a significant reduction in the expression of interleukin (IL)–8, interferon inducible protein–10, IL‐17a, interferon‐γ, IL‐10, and IL‐12 across the aforementioned groups. Conclusions: Patients diagnosed with PANDAS appear to maintain significantly different concentrations of cytokines when compared with patients afflicted by chronic group A beta hemolytic streptococcus infections and obstructive sleep apnea. As a result, one could potentially use the described characterization of immunologic markers as a basis for future mechanistic and epidemiological studies.